Comparison of the Immunogenicity of HIV-1 CRF07_BC Gag Antigen With or Without a Seven Amino Acid Deletion in p6 Region - Li, Minchao; Yuan, Yue; Li, Pingchao; Deng, Zhaomin; Wen, Ziyu; Wang, Haiying; Feng, Fengling; Zou, Huachun; Chen, Ling; Tang, Shixing; Sun, Caijun (Frontiers in Immunology, 2022)
HIV-1 CRF07_BC-p6Δ7, a strain with seven amino acid deletion in the p6 region of the Gag protein, is becoming the dominant strain of HIV transmission among men who have sex with men (MSM) in China. Previous studies demonstrated that HIV-1 patients infected by CRF07_BC-p6Δ7 strain had lower viral load and slower disease progression than those patients infected with CRF07_BC wild-type strain. However, the underlying mechanism for this observation is not fully clarified yet. In this study, we constructed the recombinant DNA plasmid and adenovirus type 2 (Ad2) vector-based constructs to express the HIV-1 CRF07_BC Gag antigen with or without p6Δ7 mutation, and then investigated their immunogenicity in mice. Our results showed that HIV-1 CRF07_BC Gag antigen with p6Δ7 mutation induced a comparable level of Gag-specific antibodies but a stronger CD4+ and CD8+ T immune response than that of CRF07_BC Gag (07_BC-wt). Furthermore, we identified a series of T cell epitopes, which induced strong T cell immune response and cross-immunity with CRF01_AE Gag. These findings implied that the p6Gag protein with seven amino acid deletion in p6 region might enhance the immunogenicity of Gag in particular cellular immunity, which provides valuable information for the development of precise vaccine strategies against HIV-1 infection.